Respuesta :

Answer:

we determine that none of the ordered pair is a solution of  [tex]3y\:+\:2\:=\:2x\:-\:5[/tex]  as none of the ordered pairs satisfy the equation.

Step-by-step explanation:

Considering the equation

[tex]3y\:+\:2\:=\:2x\:-\:5[/tex]

  • Putting (-5,2) in the equation

[tex]3y\:+\:2\:=\:2x\:-\:5[/tex]

[tex]3\left(2\right)\:+\:2\:=\:2\left(-5\right)\:-\:5[/tex]

[tex]8=-15[/tex]         ∵ L.H.S ≠ R.H.S

FALSE

  • Putting (0,-5) in the equation

[tex]3y\:+\:2\:=\:2x\:-\:5[/tex]

[tex]3\left(-5\right)\:+\:2\:=\:2\left(0\right)\:-\:5[/tex]

[tex]-13=-5[/tex]       ∵ L.H.S ≠ R.H.S

FALSE

  • Putting (5,1) in the equation

[tex]3y\:+\:2\:=\:2x\:-\:5[/tex]

[tex]3\left(1\right)+\:2\:=\:2\left(5\right)-\:5[/tex]

[tex]5\:=-5[/tex]          ∵ L.H.S ≠ R.H.S

FALSE

  • Putting (7,5) in the equation

[tex]3y\:+\:2\:=\:2x\:-\:5[/tex]

[tex]3\left(5\right)+\:2\:=\:2\left(7\right)-\:5\:\:[/tex]

[tex]17=9[/tex]          ∵ L.H.S ≠ R.H.S

FALSE

From the above calculations, we determine that none of the ordered pair is a solution of  [tex]3y\:+\:2\:=\:2x\:-\:5[/tex]  as none of the ordered pairs satisfy the equation.

ACCESS MORE